Are Pharmacists Participating in Postdischarge Patient Reminders? - Felkey, Bill G. (Hosp Pharm, 2017)
In this column, we are making a short revisit to the technology that can assist in satisfaction of Meaningful Use criteria and can assist health systems that are increasing their population health initiatives to help improve outcomes while containing costs.